"Ne me dis pas que tu crois aux signes": formes et métamorphoses des Formidables aventures de Lapinot de Lewis Trondheim. Issue 1 (4th January 2021) - Dépinoy, Denis
ABSTRACT: Framing Lewis Trondheim's Formidables aventures de Lapinot as a critical take on Franco-Belgian serial bandes dessinées, this article examines how Trondheim explores and exhausts the constraints associated with the medium, and particularly the notions of forms, characters, and roles. Changing, unstable, and reimagined character-spaces and character-systems suggest the metamorphosis of the eponymous character from a function into a sign. The character not only operates within the formal and narrative systems of classic bandes dessinées but also acts, through a series of transformations, as a sign of these systems.